Device-Based Sympathetic Nerve Regulation for Cardiovascular Diseases - Li, Le; Hu, Zhao; Xiong, Yulong; Yao, Yan (Frontiers in Cardiovascular Medicine, 2021)
Sympathetic overactivation plays an important role in promoting a variety of pathophysiological processes in cardiovascular diseases (CVDs), including ventricular remodeling, vascular endothelial injury and atherosclerotic plaque progression. Device-based sympathetic nerve (SN) regulation offers a new therapeutic option for some CVDs. Renal denervation (RDN) is the most well-documented method of device-based SN regulation in clinical studies, and several large-scale randomized controlled trials have confirmed its value in patients with resistant hypertension, and some studies have also found RDN to be effective in the control of heart failure and arrhythmias. Pulmonary artery denervation (PADN) has been clinically shown to be effective in controlling pulmonary hypertension. Hepatic artery denervation (HADN) and splenic artery denervation (SADN) are relatively novel approaches that hold promise for a role in cardiovascular metabolic and inflammatory-immune related diseases, and their first-in-man studies are ongoing. In addition, baroreflex activation, spinal cord stimulation and other device-based therapies also show favorable outcomes. This review summarizes the pathophysiological rationale and the latest clinical evidence for device-based therapies for some CVDs.